Heliconiaceae in the metropolitan region of Belém, state of Pará, Brazil - Cardoso, Jesiane Miranda; Bragança Gil, André dos Santos; Hall, Climbiê Ferreira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
We performed the taxonomic treatment of the species of Heliconiaceae from the metropolitan region of Belém (RMB), State of Pará, Brazil. In Brazil, 25 species of Heliconiaceae are registered, of which 23 are found in the Amazon and eight in the state of Pará. The RMB is composed by seven municipalities: Belém, Ananindeua, Benevides, Castanhal, Marituba, Santa Bárbara do Pará and Santa Isabel do Pará. The region is located within the area of endemism of Belém and underwent urbanization in its forest areas, but still presents forest fragments preserved and protected. We studied species collected in the RMB and collections from the herbaria of Museu Goeldi (MG) and EMBRAPA (IAN). We found seven species of Heliconiaceae in the RMB: Heliconia acuminata, H. adeliana, H. hirsuta, H. psittacorum, H. richardiana, H. rostrata and H. spathocircinata. We present a taxonomic key, descriptions, comments and illustrations of the species.